Intermediates in organometallic photochemistry - Haynes, Anthony (1989)
CHAPTER 1: A background to the techniques of matrix isolation, liquid xenon solution and flash photolysis with fast IR detection is presented. The application of infrared spectroscopy in structural studies of metal carbonyl compounds is also discussed. Chapter 2: Photolysis of((nu5-C5R5)Pt(CO))2 (R=H, Me) in frozen gas matrices results in production of ((nu5-C5R5)Pt2(mu-CO)). 13CO enrichment and polarised photochemistry show that the photoproduct contains a single symmetrically bridging CO group. Photolysis of (CpNi(mu-CO))2 in frozen gas matrices results in formation of CP2Ni2(CO) with a terminal CO ligand. The stability these dinuclear photoproducts in room temperature solution has been investigated using fast TRIR spectroscopy. Photolysis in CO matrices leads to M-M bond cleavage and reaction with CO to give Pt(CO)4 or Ni(CO)4 as the final product. CHAPTER 3: Photolysis of Os2(CO)9 or OS2(CO)8- - (mu-nu1, nu1-C2H4) in frozen gas matrices leads to formation of Os2(CO)8, which has only terminal CO groups. The thermal and photochemical reactivity of Os2(CO)a towards CO, N2 and C2H4 is investigated. Photolysis using plane polarised light provides confirmation of the C2v structure of Os2(CO)9, and gives evidence favouring a D2h structure for Os2(CO)8. Prolonged UV photolysis of Os2(CO)9 in CO matrices leads to cleavage of the Os-Os bond and production of Os(CO)5. CHAPTER 4: The mechanism of the photochemical deoligomerisation of FpSiMe2SiMe3 is investigated using a variety of techniques. The reaction is shown to proceed via two photochemical steps. Primary CO-loss is followed by intramolecular trapping to give a silyl(silylene) intermediate. The second step involves expulsion of an SiMe2 fragment and coordination of a ligand. L. to give CpFe(CO)(L)SiMe3 (L = CO, PPh3,C2H4 or N2). CHAPTER 5: A study of the photochemistry of Fp-disilyl complexes containing beta-silyl hydrogens implies beta-H transfer from Si to Fe as the dominant process following photodissociation of CO. The product, a metalladisilacyclopropane or nu2-disilene complex, is implicated as an intermediate in the photochemical formation of FpH in this system. CHAPTER 6: The experimental techniques and spectrometers used in this research are described. along with a discussion of the theory and advantages of FTIR spectroscopy.